Pacing strategy during Olympic Cross-Country Mountain Bike: effects of performance level, age and sex - do Carmo, E. C.; Inoue, A.; Cal Abad, C. C.; dos Santos Andrade, F. A.; Tricoli, V.; Barroso, R. (Journal of Science and Cycling, 2020)
Objectives: the aim of the present study was to verify the pacing strategy during a season of a Cross-Country Mountain Bike (XCO-MTB) and the effects of performance level, age and sex. Method: Overall, 802 paces in 4 age-sex categories were analyzed: male elite (EliteM; n = 272), female elite (EliteF; n = 170), male under-23 (U23M; n = 247) and female under-23 (U23F; n = 113). Races were divided into Initial Lap; middle one (Middle1); middle two (Middle2) and Final Lap. The athletes were divided into high performance (HP); intermediated performance (IP) and low performance (LP). The magnitude-based inference and the effect size were assessed to check the changes clinically important. Results: it was observed a similar fast-start strategy for all categories. Both HP EliteM and EliteF athletes showed higher speed in Final Lap than LP (EliteM -ES = 0.5; 90%CI -0.8 to -0.2; very likely and EliteF -ES = 1.0; 90%CI -1.4 to -0.6; almost certain). The U23F athletes showed higher speeds in Initial Lap than EliteF (ES = 0.21; 90%CI -0.1to 0.5; likely), however in Final Lap the speeds was lower in U23F (ES = 1; 90%CI -1.3 to -0.6; very likely). Conclusion: the fast-start strategy is typically used during a XCO-MTB race independently of performance level, age or sex. HP Elite athletes areable to maintain higher speeds in the Final Lap. U23F athletes used to do a more variable pacing strategy with more aggressive fast-start strategy and lower speed in Final Lap than EliteF.